INDUSTRI GALANGAN KAPAL KAYU DI PESISIR RIAU - Ahmad, Muchtar; Nofrizal, Nofrizal (Jurnal Perikanan dan Kelautan, 2013)
Base on the survei and field visiting at the location of dockyard industry, thestate of traditional dockyard management and technology reported. Traditionaldockyards use wood as raw materials for building mostly small fishing boat of less than5 GT. The location of dockyard is built open on the bank of riverside in the coastal areawithout any covered building. Facilities in the traditional dockyard as well asinfrastructure ro the location are almost nothing deliberately built. The dockyardpersists on the wetland environment, swampy area, and unhealthy working condition.The management of the dockyard is family wise as it belongs to the one core family, butthe boat craft man mostly recruite from extended family. While the technology usedmostly come from the long experiences working in the famili or other dockyard. Themain problem of the traditional dockyard is the raw wood materials are scarce anddifficult to get it, except by high price, whilst capital to secure materials stockunavailable. The consequence, five of seven traditional dockyard surveied have beenstopping to product a new boat; and frustrating to pace the future. The probableeffective idea of way out to the situation is to use alternative wooden materialsubstitution such as FRP.